2020
DOI: 10.2139/ssrn.3535290
|View full text |Cite
|
Sign up to set email alerts
|

Housing Search Frictions: Evidence from Detailed Search Data and a Field Experiment

Abstract: Any opinions expressed in this paper are those of the author(s) and not those of IZA. Research published in this series may include views on policy, but IZA takes no institutional policy positions. The IZA research network is committed to the IZA Guiding Principles of Research Integrity. The IZA Institute of Labor Economics is an independent economic research institute that conducts research in labor economics and offers evidence-based policy advice on labor market issues. Supported by the Deutsche Post Founda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Another alternative to customized housing search assistance is to provide information in a more standardized manner. Bergman, Chan, and Kapor (2019) randomized the provision of information to families about the quality of schools associated with rental units on GoSection8.com, a housing search platform widely used by voucher holders. They find small positive impacts of this low-cost intervention on the fraction of families who move to areas with better schools, with treatment effects considerably smaller than those induced by CMTO.…”
Section: Viib Effects Of Information Provisionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another alternative to customized housing search assistance is to provide information in a more standardized manner. Bergman, Chan, and Kapor (2019) randomized the provision of information to families about the quality of schools associated with rental units on GoSection8.com, a housing search platform widely used by voucher holders. They find small positive impacts of this low-cost intervention on the fraction of families who move to areas with better schools, with treatment effects considerably smaller than those induced by CMTO.…”
Section: Viib Effects Of Information Provisionmentioning
confidence: 99%
“…Schwartz, Mihaly, and Gala (2017) report results from a randomized trial showing that short-run financial incentives and light-touch counseling had little impact on the rate of moves to higher opportunity areas in Chicago. Bergman, Chan, and Kapor (2019) randomized the provision of information to families about the quality of schools associated with rental units on a website commonly used by voucher holders. The information intervention resulted in moves to units with slightly better neighborhood schools, but had a much smaller impact 6.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers, primarily in economics, have thus been interested in how information interventions could influence families' applications to schools. Several experimental studies have found that when low-income and non-English speaking families are provided with more information about schools with high test scores or graduation rates, they are more likely to apply to and enroll in one of those schools [5,11,22,24,43,59]. This kind of data about schools is increasingly available to parents, as government and non-profit organizations have produced tools to make school accountability data available on a larger scale, e.g., GreatSchools.org 7 or the California Schools Dashboard 8 (Figure 1).…”
Section: Information and School Choicementioning
confidence: 99%
“…Another is that emphasizing quantitative measures, especially test scores, disadvantages schools that serve more low-income students and English learners [8]. This could exacerbate segregation if more privileged families use this information to avoid these schools [11,12].…”
Section: Information and School Choicementioning
confidence: 99%
“…Our research is also part of a growing body of work that combines surveys, experiments, and structural estimation, such as Benjamin, Heffetz, Kimball, and Rees-Jones (2014) who study life satisfaction of students who submit choice rankings to medical schools, and Galiani, Murphy, and Pantano (2015) who use the moving to opportunity experiment to simulate the effect of changes in the subsidies, Bottan and Perez-Truglia (2017) who apply information surveys to medical students in order to understand the importance of relative income in city-level choices, and Bergman, Chan, and Kapor (2020) who study the role of imperfect information about school quality.…”
Section: Introductionmentioning
confidence: 99%